Judaic Technologies of the Word A Cognitive Analysis of Jewish Cultural Formation - Levy, Gabriel (London ; New York : Routledge, Taylor & Francis Group, 2014)
Judaic Technologies of the Word argues that Judaism does not exist in an abstract space of reflection. Rather, it exists both in artifacts of the material world - such as texts - and in the bodies, brains, hearts, and minds of individual people. More than this, Judaic bodies and texts, both oral and written, connect and feed back on one another. Judaic Technologies of the Word examines how technologies of literacy interact with bodies and minds over time. The emergence of literacy is now understood to be a decisive factor in religious history, and is central to the transformations ...
What is cognition? -- Control -- Networks -- Rationality -- Names -- Hypertext -- Environment.
Description based upon print version of record.
Keywords: Judaism -- History -- Philosophy; Literacy -- Religious aspects -- Judaism; Judaism and culture; Communication and culture; Communication and culture; Judaism -- History -- Philosophy; Judaism and culture; Literacy -- Religious aspects -- Judaism; RELIGION / Judaism / General; Electronic books